1985
DOI: 10.1161/01.cir.71.1.31
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of relationship between myocardial contractile state and left ventricular function in patients with aortic regurgitation.

Abstract: We studied the relationship between myocardial contractile state and left ventricular functional response to exercise in 14 asymptomatic patients with isolated moderate-to-severe aortic regurgitation and six control subjects. The slope of the systolic blood pressure-left ventricular endsystolic volume (pressure-volume) relationship determined by radionuclide ventriculography during angiotensin infusion was used as an indirect measure of myocardial contractility and was compared with left ventricular ejection f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1988
1988
2008
2008

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…4 6 7 Borer and colleagues reported that patients whose ejection fraction decreased on exercise by more than 5% had a 12.5%/year risk of developing heart failure or subclinical left ventricular dysfunction, compared with only 1.9%/year if the ejection fraction response was normal; the risk was 8.8%/year if the ejection fraction on exercise was less than 50% 4. We applied the same cut off to differentiate between patients with good and poor exercise responses; a fall in ejection fraction on exercise of less than 5% was taken as no change, as this value—used by Borer and colleagues—corresponded to more than 2 SD of our intraobserver variability for this measurement.…”
Section: Discussionmentioning
confidence: 99%
“…4 6 7 Borer and colleagues reported that patients whose ejection fraction decreased on exercise by more than 5% had a 12.5%/year risk of developing heart failure or subclinical left ventricular dysfunction, compared with only 1.9%/year if the ejection fraction response was normal; the risk was 8.8%/year if the ejection fraction on exercise was less than 50% 4. We applied the same cut off to differentiate between patients with good and poor exercise responses; a fall in ejection fraction on exercise of less than 5% was taken as no change, as this value—used by Borer and colleagues—corresponded to more than 2 SD of our intraobserver variability for this measurement.…”
Section: Discussionmentioning
confidence: 99%
“…In 1 study (275), the LV ejection fraction during exercise was an independent risk factor. However, the direction and magnitude of change in ejection fraction from rest to exercise is related not only to myocardial contractility (279) but also to severity of volume overload (271,278 -280) and exercise-induced changes in preload and peripheral resistance (280). In 2 multivariate analyses (271,276), only age and end-systolic dimension on initial study were independent predictors of outcome, as were the rate of increase in end-systolic dimension and decrease in resting ejection fraction during serial longitudinal studies (271).…”
Section: Natural Historymentioning
confidence: 99%
“…In 1 study, 275 the LV ejection fraction during exercise was an independent risk factor. However, the direction and magnitude of change in ejection fraction from rest to exercise is related not only to myocardial contractility 279 but also to severity of volume overload 271,278 -280 and exerciseinduced changes in preload and peripheral resistance. 280 In 2 multivariate analyses, 271,276 only age and end-systolic dimension on initial study were independent predictors of outcome, as were the rate of increase in end-systolic dimension and decrease in resting ejection fraction during serial longitudinal studies.…”
Section: Pathophysiologymentioning
confidence: 99%